2013
DOI: 10.3390/molecules18043825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Freshwater Clam Extract Supplementation on Time to Exhaustion, Muscle Damage, Pro/Anti-Inflammatory Cytokines, and Liver Injury in Rats after Exhaustive Exercise

Abstract: The potent anti-inflammatory activities and tissue-protective effects of freshwater clams (Corbicula fluminea) have been well reported. The aim of this study was to determine the effects of freshwater clam extract (FCE) supplementation on time to exhaustion, muscle damage, pro- and anti-inflammatory cytokines, and liver injury in rats after exhaustive exercise. Thirty-two rats were divided into four groups: sedentary control (SC); SC group with FCE supplementation (SC+FCE); exhaustive exercise (E); and E group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…19 Comparable results were found by DelghingaroAugusto et al that examined diabetic rats subsequent 6 weeks of voluntary wheel running. 20 Nevertheless, exhaustive exercise may be problematic, as they are stressful through production of reactive oxygen species and can cause damage to muscle tissue and other organs, 21 voluntary exercise may be a better model with more beneficial effects. 22 In the animal model of voluntary exercise, the animal has free access to a running wheel and uses the wheel according to its physiological threshold for physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…19 Comparable results were found by DelghingaroAugusto et al that examined diabetic rats subsequent 6 weeks of voluntary wheel running. 20 Nevertheless, exhaustive exercise may be problematic, as they are stressful through production of reactive oxygen species and can cause damage to muscle tissue and other organs, 21 voluntary exercise may be a better model with more beneficial effects. 22 In the animal model of voluntary exercise, the animal has free access to a running wheel and uses the wheel according to its physiological threshold for physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…11 Intense exercise induces liver damage, resulting in aminotransferase release, oxidative stress, and ultrastructural abnormalities. 7 Here we showed that liver inflammation subsequent to such damage was driven by increased TNF-α concentration. TNF-α, a primary biomarker of tissue injury, activates T cells and macrophages and upregulates other proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 87%
“…These animals also show increased serum levels of the proinflammatory cytokine tumor necrosis factor α (TNF-α), and histological evaluation reveals periportal leukocyte infiltration and hepatocyte vacuolization. 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…The goal of the additional treatment rather than western medicine is to improve the life quality of the patient at the acute stage, including vital signs stabilization, soft tissue swelling faster subsidence and smooth wound healing (16). In previous studies, FCE appeared to effectively suppress the release of pro-inflammatory TNF-α after hemorrhagic shock and protect the liver function of the experimental animals (17,18). The characteristic of anti-inflammatory and liver protection may benefit acute stage of traumatic fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic of anti-inflammatory and liver protection may benefit acute stage of traumatic fracture. Establishment of a conscious rat model (9,17) to observe the effect of FCE on the acute stage of a fracture can simulate our recording vital signs two or three times a day for closely observation the influence of medical therapy on the acute stage. We recorded vital signs of the rats to monitor their instant conditions during the experimental period.…”
Section: Discussionmentioning
confidence: 99%